Impact of the T296S mutation in P450 GcoA for aryl-O-demethylation: a QM/MM study - Santos, Sonia F. G.; Bommareddy, Rajesh Reddy; Black, Gary W.; Singh, Warispreet (Frontiers in Chemistry, 2024)
Lignin, a complex plant cell wall component, holds promise as a renewable aromatic carbon feedstock. p-Vanillin is a key product of lignin depolymerization and a precursor of protocatechuic acid (PCA) that has tremendous potential for biofuel production. While the GcoAB enzyme, native to Amycolatopsis sp., naturally catalyzes aryl-O-demethylation toward guaiacol, recent research introduced a single mutation, T296S, into the GcoAP450 enzyme, enabling it to catalyze aryl-O-demethylation of p-vanillin. This structural modification increases the efficiency of GcoAP450 for the natural substrate while being active for p-vanillin. This study reveals the increased flexibility of p-vanillin and its ability to adapt a favorable conformation by aligning the methoxy group in close proximity to Fe(IV) = O of Cpd I in the active site of the T296S variant. The QM/MM calculations in accordance with the experimental data validated that the rate-limiting step for the oxidation of p-vanillin is hydrogen atom abstraction and provided a detailed geometric structure of stationary and saddle points for the oxidation of p-vanillin.